Public Service Announcements and Promoting Face Masks During the COVID-19 Pandemic. Issue 1 (10th January 2022) - Greene, Steven; Hetherington, Marc; Maxwell, Rahsaan; Ryan, Timothy J.
ABSTRACT: Wearing face masks to combat the spread of COVID-19 became a politicized and contested practice in the United States, largely due to misinformation and partisan cues from masking opponents. This article examines whether Public Service Announcements (PSAs) can encourage the use of face masks. We designed two PSAs: one describes the benefits of using face masks; the other uses a novel messenger (i.e., a retired US general) to advocate for them. We conducted two studies. First, we aired our PSAs on television and surveyed residents of the media market to determine if they saw the PSA and how they felt about wearing face masks. Second, we conducted a randomized experiment on a diverse national sample. Both studies suggest that exposure to our PSAs increased support for face masks and induced greater compliance with public health advice. These findings have implications for how governments might fight pandemics.